FORM MAKING AS A PROBLEM OF PHILOSOPHICAL AND AESTHETIC ANALYSIS - S. Bastrykina, Tatyana; Yu. Belyakovsky, Boris; N. Kepa, Yuri (Revista Gênero e Interdisciplinaridade, 2020)
The development of mass communication, the widespread computerization, as well as the development of technical forms of art, such as cinema, photography and advertising, and, in general, raising the level of civilization gives rise to a new way of perception and creativity, changes the spiritual culture, and influences the form making of mass consciousness. Under such conditions, the transformation of the sphere of cognition in general is obvious, allowing one to identify new aspects of scientific knowledge, as well as the specifics of new disciplines that arose at the junction of traditional scientific fields (semiotics, cybernetics, information theory, etc.), and requiring philosophical reflection. The boundaries of not only scientific disciplines, but also of the types of art, become mobile. Montage, which was born as a technical tool of cinema, developed into the principle of montageability becoming as a result (like the two other favourite methods of postmodernism, collage and quotation) a thing, which determines everything for each mentality, including creative one. The relevance of the study is determined by the fact that in many works devoted to the study of the fashion phenomenon, sometimes there is an unconscious mixture of the concepts of “fashion” and “modelling of a suit,” and, in particular, of their aesthetic functions, which does not allow us to fully identify the specifics of “clothing design” as a direction in designing. Moreover, until now, significant changes in the worldview of the XX century have not been reflected in the theory of fashion, in particular, in such its part as the shaping of a costume, and they can affect both the nature of the phenomenon itself and the fundamental principles in the field of costume design.